Software tools and platforms in Digital Pathology: a review for clinicians and computer scientists - Escobar Díaz Guerrero, Rodrigo; Carvalho, Lina; Bocklitz, Thomas; Popp, Juergen; Oliveira, José Luis (Journal of Pathology Informatics, 2022)
At the end of the twentieth century, a new technology was developed that allowed an entire tissue section to be scanned on an objective slide. Originally called virtual microscopy, this technology is now known as Whole Slide Imaging (WSI). WSI presents new challenges for reading, visualization, storage, and analysis. For this reason, several technologies have been developed to facilitate the handling of these images. In this paper, we analyze the most widely used technologies in the field of digital pathology, ranging from specialized libraries for the reading of these images to complete platforms that allow reading, visualization, and analysis. Our aim is to provide the reader, whether a pathologist or a computational scientist, with the knowledge to choose the technologies to use for new studies, development, or research.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Computational pathology; Digital Pathology; Image analysis; Pathomics; Whole Slide Imaging